BUMI: ANTARA BULAT DAN DATAR? - Darlis . (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
The debate over the shape of the Earth, whether flat or spherical, is not only a scientific issue but also a matter of interpretation. The conclusions of proponents of a flat Earth and a spherical Earth both stem from the same interpretation of verses. This research is a literature review based on interpretations and articles related to the issue. The approach used is a comparative study and uses semantic analysis of verses in the Qur'an that convey the meaning of